Kindergarten Teachers’ Perspective on Early Intervention in Autism Spectrum Disorders - Caeiro, Ana Paula; Franco, Vítor (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
In Portugal, children with developmental disorders are supported by the National Early Childhood Intervention System (NECIS). This network aims to promote child development from a family-centered perspective, based on community support and carried out in everyday natural contexts by a transdisciplinary team. This study aims to verify how the NECIS responds to the needs identified by educators who receive children with Autism Spectrum Disorder (ASD) in pre-school. This is a qualitative, multiple case study using the content analysis of 6 semi-structured interviews. The results show that these educators feel ill-prepared to work with children with ASD. They expect NECIS professionals will perform more targeted and rehabilitative work with the child and point out the limited time that they have to spend with children as one of the main constraints.